Testing and Measurement of Operational Amplifier - Jindal, Sourabh (My University, 2015)
Today, the operational amplifier is the most important analog device which is being used in almost all the electronic system. Every electronic system has its own requirement. So it is very necessary to measure the specification of the Op-Amp before using it in the respective application. The present work, proposes a servo Op-Amp based test circuit for the measurement of the performance parameters of the Op-Amp. An extra Op-Amp is added in the feedback loop which is acting as an attenuator. By doing this it is possible to completely reject any input signal feed-through from the feedback loop. So an extra Op-Amp completely decouples the output from the input. Simulations of the test circuit are performed using a spice based simulator MULTSIM. TLV2772CP, a CMOS based Op-Amp is used as the device under test. Verification of the simulated results is being done by the using a measurement setup on the bread board in the laboratory and the results are compared with the data sheet of the DUT.
Master of Technology (VLSI Design)
Keywords: Measurement in Op-Amp; open loop gain; CMRR; PSRR; Electornics and Communication; ece